Educação e cultura corporal - análise da dança e reflexões sobre a cisão corpo e mente no curso de pedagogia da FE/UFG - Oliveira, Amanda Almeida de (2023)
In making this work, we sought to answer the question: Does the discipline Education and Corporal Culture offered in the Pedagogy course at the Faculty of Education at UFG work on dance by bringing reflections on the separation body and mind? First, a study was carried out on what would be the separation between body and mind and its historical aspects. Then it was possible to understand some of the consequences of the separation in society, in the schools and in art. A brief understanding of the history of dance was sought. Then, we started to discuss the relevance of dance in teacher education. After these reflections, the analyzes of some curricula of different Pedagogy courses from Brazilian universities were presented to understand if dance is present in this formation. Then, the Pedagogical Political Project of the Pedagogy Course of the Faculty of Education of UFG and the syllabus and bibliography of the discipline Education and Corporal Culture were analyzed. From the bibliography, works that apparently address the theme of dance and the separationting of body and mind were selected for analysis. The work was based on the theoretical conception entitled “dialectical historical materialism”. Finally, it was possible to observe that reflections on the separation between body and mind are raised in the analyzed discipline, through the texts presented in the bibliography. However, there is still a long way to go so that dance, being significant to raise questions about the separation between body and mind, has a space of equality before other areas of knowledge in the formation of Pedagogues.